2020
DOI: 10.1186/s12284-020-00389-1
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-Wide Analyses Reveal the Diverse Functions of Lysine 2-Hydroxyisobutyrylation in Oryza sativa

Abstract: Background: Lysine 2-hydroxyisobutyrylation (Khib), a newly identified post-translational modification, is known to regulate transcriptional activity in animals. However, extensive studies of the lysine 2-hydroxyisobutyrylome in plants and animals have yet to be performed. Results: In this study, using LC-MS/MS qualitative proteomics strategies, we identified 4163 Khib sites on 1596 modified proteins in rice (Oryza sativa) seedlings. Motif analysis revealed 10 conserved motifs flanking the Khib sites, and subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 53 publications
4
39
1
Order By: Relevance
“…The overall trend of GO classification (including biological process, molecular function and cellular components) and subcellular localization of K hib proteins identified in rhubarb were similar to previous findings obtained in other plants such as P. patens [10] and rice [12], although the percentages of each category were slightly different.…”
Section: Characterization Of K Hib Modification Proteins Identified In Rhubarbsupporting
confidence: 85%
See 2 more Smart Citations
“…The overall trend of GO classification (including biological process, molecular function and cellular components) and subcellular localization of K hib proteins identified in rhubarb were similar to previous findings obtained in other plants such as P. patens [10] and rice [12], although the percentages of each category were slightly different.…”
Section: Characterization Of K Hib Modification Proteins Identified In Rhubarbsupporting
confidence: 85%
“…Previous studies on both eukaryotic and prokaryotic cells have found a preference for specific amino acid residues around the K hib site [10][11][12]14]. Therefore, we utilized the Motif-X tool, software for extracting Fig.…”
Section: Analysis Of K Hib -Modified Peptides Reveals Conserved Motifsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein extraction and trypsin digestion were performed referring previous report with some modifications [ 20 ]. In brief, wheat leaves were grinded into powder in a mortar with the addition of liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…After incubation, rinse the beads for 4 times with NETN buffer and 2 times with purified water. Elute the captured modified peptides with 0.1% Trifluoroacetic acid and vacuum dry them [ 20 ].…”
Section: Methodsmentioning
confidence: 99%